21‐1: Invited Paper: Technology Trend and Challenges for MicroLED Large Display Applications - Chen-Ke, Hsu (SID International Symposium Digest of technical papers, 2023)
MicroLED is good technology for fine pitch (<P1.0) large display applications. From the TV and LED display history trend, people like larger display and better picture quality for immersion illusion. MiniLED COB become the main trend from year 2019, and next coming MicroLED technology is obviously direction. Sony already has CLEDIS in B and C series in the market. Samsung announced that MicroLED COG Display in 89", 101" and 114" in 2023 CES. This talk will be focus on MicroLED technologies for fine pitch large display. POB, POG and COG are technologies for different driving platform and their own advantages. MiP (MicroLED in Package) technology demonstrates advantages for fine pitch large display application.